THE EFFECT OF PAYMENT THROUGH QUICK RE-SPONSE INDONESIAN STANDARD (QRIS) ON CUS-TOMER SATISFACTION OF MICRO, SMALL AND ME-DIUM ENTERPRISES (MSMES) IN RIAU PROVINCE - Pertiwi, R. Nur Aini (Inovbiz: Jurnal Inovasi Bisnis, 2024)
In the realm of digital payment systems, the adoption of Quick Response Indonesian Standard (QRIS) represents a significant advancement, promising efficiency and convenience in the digital economy. This study investigates the impact of QRIS on customer satisfaction within Micro, Small, and Medium Enterprises (MSMEs) in Riau Province. Through a quantitative approach and purposive sampling of 400 respondents, the research employs multiple linear regression analysis, validity tests, reliability tests, T-tests, and coefficient of determination (R²) using IBM SPSS version 25. The findings indicate a statistically significant positive relationship between QRIS usage and customer satisfaction among MSMEs in Riau Province. The study contributes valuable insights into the digital payment ecosystem's role in enhancing customer satisfaction, offering strategic guidance for businesses and policymakers. The R² value of 0.759 underscores QRIS variables' substantial explanatory power (75.9%) in influencing customer satisfaction within MSMEs, illuminating avenues for further exploration and application in digital payment innovations.